Communication Infrastructure for Monitoring Heart Rate of Patients on The Cloud Using IoT Devices (2017)
Methods for carrying out clinical patient histories and their subsequent monitoring have been presented for several decades. Today, has awakened the interest of many health areas, determine mechanisms that allow patients to be monitored at low cost, by capturing events in devices that are used through the Internet of Things. The purpose of this article is to present a communication infrastructure proposal for the capture of a person's heartbeats through sensors and their subsequent storage in the cloud via wireless to a server. Factors that affect the response times of these systems are addressed through asynchronous task queuing.